2022
DOI: 10.1007/s12520-022-01631-1
|View full text |Cite
|
Sign up to set email alerts
|

Negative muons reveal the economic chaos of Rome’s AD 68/9 Civil Wars

Abstract: During the AD 68/9 Civil Wars, Galba, Otho, Vitellius and then Vespasian fought for — and gained — control of the Roman Empire. Our textual sources suggest that this was a period of serious and sustained disruption. However, existing analyses of gold coinages produced in AD 68/9 show only a minor reduction in the purity of the gold coinage. Using X-ray fluorescence, we identify a number of heavily debased gold coins issued during the AD 68/9 Civil Wars, and many slightly debased coins issued in their immediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…In addition, extensive simulation of the complicated geometry of archaeological objects is necessary in order to determine the attenuation of the muonic X-rays inside the archaeological material of interest (not as high as electronic X-rays, but certainly not completely negligible) for the proper determination of the elemental composition. Nevertheless, we along with the other published works so far [4,[6][7][8][9][11][12][13] have demonstrated that MIXE is a very promising new method for completely non-destructive quantitative elemental analysis of valuable objects such as archaeological cultural artefacts. An immense advantage is that, due to the high-energy muonic X-rays, the analysis technique allows measurements up to several centimetres deep-depending on the density of the sample-and thus, if necessary, measurements can be made below the corrosion layer, coatings or surface enrichments.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In addition, extensive simulation of the complicated geometry of archaeological objects is necessary in order to determine the attenuation of the muonic X-rays inside the archaeological material of interest (not as high as electronic X-rays, but certainly not completely negligible) for the proper determination of the elemental composition. Nevertheless, we along with the other published works so far [4,[6][7][8][9][11][12][13] have demonstrated that MIXE is a very promising new method for completely non-destructive quantitative elemental analysis of valuable objects such as archaeological cultural artefacts. An immense advantage is that, due to the high-energy muonic X-rays, the analysis technique allows measurements up to several centimetres deep-depending on the density of the sample-and thus, if necessary, measurements can be made below the corrosion layer, coatings or surface enrichments.…”
Section: Discussionmentioning
confidence: 97%
“…Actually, in contrast to electron-induced X-ray analysis techniques, the MIXE technique can provide results below the usually distorted surface of archaeological metal objects. Examples of applications of this analysis technique to archaeological metal objects are already available [4,[6][7][8][9][11][12][13], all of which were performed at pulsed muon beam facilities. It was also shown recently [1,2] that the unique experimental setup at the Paul Scherrer Institute (PSI), which utilizes continuous muon beams, enables one to achieve high statistics measurements in short measurement periods.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on these characteristics, the Paul Scherrer Institute (PSI) of Switzerland, Tri-University Meson Facility (TRIUMF) of Canada, and Los Alamos Meson Physics Facility (LAMPF) of the United States were the first to conduct μ-X ray elemental analysis experiments on biological materials [3][4][5][6]. The technology has since been employed in archaeology [7,8], the detection of extraterrestrial materials [9], lithium batteries [10], and other applications [2,[11][12][13]. Recently, the potential application of μ-X rays to the imaging of small objects was discovered.…”
Section: Introductionmentioning
confidence: 99%